2021
DOI: 10.1111/jfd.13537
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia Lake Virus was not detected in non‐tilapine species within tilapia polyculture systems of Bangladesh

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Our study revealed the presence of TiLV in both fish and environmental water samples from the same farm, which clustered together in Clade E1. Our approach, combining the previously reported water sample concentration method (Taengphu et al, 2022) with a multiplex RT-PCR amplicon-based Nanopore sequencing strategy, allowed for direct recovery of TiLV genomes from water samples. This innovative method has significant implications for environmental monitoring, as it eliminates the need for sacrificing fish for genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed the presence of TiLV in both fish and environmental water samples from the same farm, which clustered together in Clade E1. Our approach, combining the previously reported water sample concentration method (Taengphu et al, 2022) with a multiplex RT-PCR amplicon-based Nanopore sequencing strategy, allowed for direct recovery of TiLV genomes from water samples. This innovative method has significant implications for environmental monitoring, as it eliminates the need for sacrificing fish for genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Tilapia lake virus disease (TiLV) is a highly contagious viral disease that affects tilapia, an important and affordable fish protein source produced in aquaculture globally. TiLV has rapidly spread since, now reported in over 16 countries (Debnath et al, 2022), posing a significant threat to tilapia production and the livelihoods of farmers who rely on tilapia farming for income and food security (Hounmanou et al, 2018). To combat the introduction and spread of TiLV and its impacts, increased surveillance, improved biosecurity measures, farming practices and continuous development of effective diagnostic and sequencing methods are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreaks of tilapia lake virus (TiLV), or Tilapinevirus tilapiae, have caused significant morbidity and mortality among the tilapia population in many countries, leading to economic and social impacts on farmers who rely on tilapia aquaculture [1][2][3]. TiLV is a negative-sense single-stranded RNA virus that is currently classified under the family Amnoonviridae [4].…”
Section: Introductionmentioning
confidence: 99%
“…This data suggests that tilapia play a significant role in disease transmission to co-cultivated species, which may be a major concern for the polyculture farm if it continues to stock tilapia with other species. However, in the instance of TiLV, co-cultivated polyculture species were shown to be TiLVresistant in both field and Challenge experiments (Debnath et. Al., 2021).…”
Section: Discussionmentioning
confidence: 99%